Understanding the Independent Predictors of Dysphagia-Related Quality of Life in Stroke Survivors. - Namasivayam-MacDonald, Ashwini M.; Ayub, Aaliyeh; Najeeb, Hiba; Shune, Samantha E. (Journal of Speech, Language & Hearing Research, 2022)
Purpose: It is important to pinpoint modifiable factors contributing to reduced dysphagia-related quality of life (QoL) in order to improve treatment outcomes and patient health given that a large proportion of stroke survivors experience dysphagia. The purpose of this exploratory study was to identify the independent predictors of dysphagia-related QoL in community-dwelling stroke survivors. Method: A sample of 31 adult stroke survivors with dysphagia (M = 62 years; 23 males) and their partners (Mage = 57 years; seven males) participated in the study. Survivors were > 3 months poststroke and living with their partner. Backward regression analysis methods were employed to determine independent predictors of dysphagia-related QoL using scores from the Swallowing-Related Quality of Life questionnaire. Independent variables tested included age, employment status, receiving dysphagia treatment, number of medical conditions, level of diet modification, Stroke Impact Scale (SIS) scores, relationship with partner, partner age, partner employment status, partner burden, and partner depression. Results: Results indicated that number of survivor medical conditions, degree of diet modification, SIS emotional subscale score, and partner employment status significantly predicted dysphagia-related QoL (p < .001). More specifically, stroke survivors with more medical conditions or a partner who worked outside of the home had worse dysphagia-related QoL, and those with better mental health or a less modified diet had better dysphagia-related QoL. Conclusion: Factors related to dysphagia-related QoL are multifactorial and include both survivor and spousal variables. The results of this exploratory study highlight the need for clinicians and researchers to consider patient function and needs more wholistically to maximize perceived QoL.